Kinematic MRI Analysis of Reducible Atlantoaxial Dislocation for Decompression. (15th December 2020) - Dong, Liang; Ge, Chaoyuan; Xu, Zhengwei; Wang, Dongqi; Sun, Honghui; Hao, Dingjun
Abstract : Background . Many doctors ignored the possibility that there is still a spinal cord compression (SCC) need for decompression after atlantoaxial reduction. Reduction can be achieved on kinematic magnetic resonance imaging (MRI); thus, we want to analyze the role of kinematic MRI in reducible atlantoaxial dislocation and make a preoperative decision whether to perform decompression. Methods . 36 patients with atlantoaxial reduction on preoperative kinematic MRI in extension postures were enrolled retrospectively. Grouping was based on the condition of SCC after atlantoaxial reduction preoperatively. Group A: patients with SCC after atlantoaxial reduction on dynamic cervical MRI were treated with C1 laminectomy for decompression and atlantoaxial fixation. Group B: patients with no significant SCC, according to dynamic MRI, underwent only atlantoaxial fixation. Clinical outcomes were evaluated using JOA score for spinal cord function. Radiological outcomes were assessed by measuring spinal cord diameter on MRI. Results . The mean follow-up time was 17.1 months. Postoperative JOA score and percentage of SCC in both groups were significantly better than its preoperative score. There were no significant statistical differences in the JOA score at 12 months after surgery and the JOA improvement rate between two groups. All patients in the two groups had a lower percentage of SCC on preoperative extension MRI, compared with neutral MRI. No significant statistical differences in the spinal decompression improvement rate were observed between the two groups. Conclusions . Decompression should be performed in patients who still have significant SCC on preoperative kinematic MRI. Kinematic MRI could be used to assess SCC and decide whether to perform decompression preoperatively.